PENGARUH DISKON DAN KEMUDAHAN LAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI APLIKASI GOFOOD PADA GENERASI Z DI KOTA PAYAKUMBUH DALAM PERSPEKTIF EKONOMI ISLAM - Nofiana, Nisa; Muhammad Rais; Awaluddin; Faisal Hidayat (JSE: Jurnal Sharia Economica, 2025)
This paper aims to examine the influence of discounts and ease of service on purchasing decisions through the GoFood application among Generation Z in Payakumbuh City, from an Islamic economic perspective. The writing population includes all GoFood users from the Gen Z group in the area. The approach applied is quantitative, and 100 respondents were given a questionnaire to fill out to collect data. The data that has been collected is then analyzed using the multiple linear regression method processed through SPSS version 21. To ensure the regression findings are valid, unbiased, and consistent, a classical assumption test was conducted before the regression analysis. The findings of the writing show that both partially and simultaneously, discounts and ease of service show a positive and significant influence on purchasing decisions. In an Islamic economic perspective, discount practices and services that make it easier for consumers as long as they do not contain elements of gharar, maysir, and usury, are considered to be in accordance with sharia principles, because they prioritize the benefit and fairness in transactions.